FREE FATTY ACIDS PROFILING IN RESPONSE TO CARNITINE SYNERGIZE WITH LUTEIN IN DIABETIC RATS - AL-Malki, Abdulrahman L; Moselhy, Said S (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The objective of this study was to investigate the fatty acids profiling in diabetic rats induced by sterptozocine (STZ) and their response to administration of lutein and carnitine. Materials and methods: Ninety male albino rats were divided into 6 groups as follows: Normal control. The remaining rats were injected i.p a single dose of STZ (65 mg /kg bw) for induction of diabetes. Diabetic rats were grouped as: GP II: (Untreated): GP III: Rats were given orally with L-lutein (100 mg/kg bw).GP IV: Rats were given carnitine (30 μg/kg) i.p. GP V: Rats were given carnitine and lutein GP VI were given metformin (100mg/kg bw/d) for 6 weeks. Results: Treatment of diabetic rats with lutein, L-carnitine, combined decreased the levels of glucose, HA1C compared with untreated diabetic (p<0.001). Administration of L-lutein, carnitine, combined to normal rats significantly decreased the levels of myristic, palmitice, palmitoleic, stearic, linoleic, α-linolenic, arachidic and eicosadienoic when compared with control normal rats (p<0.001). Conclusion: Abnormalities of fatty acids composition was observed in diabetic rats. Combination treatment with lutein and carnitine could ameliorate deleterious effect induced by STZ and attenuate the changed fatty acid composition